2018
DOI: 10.1371/journal.pone.0206352
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents have unfavorable opinions of adolescents who use e-cigarettes

Abstract: IntroductionWhile evidence suggests positive opinions of smokers are associated with tobacco use, research exploring adolescents’ opinions of e-cigarette users is nascent. We hypothesized that adolescents harbor positive opinions of e-cigarette users, and that these opinions will be more positive among adolescents willing to try or who have used e-cigarettes.MethodsParticipants were 578 U.S. adolescents (ages 14 to 20) recruited from ten California schools. An online survey assessed their attitudes toward and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Extending prior research, some participants described negative perceptions of peer‐ and influencer‐generated alcohol content, including that peers may be exhibiting poor judgement and that influencers may be ‘selling out’ or mis‐using their platform. This is consistent with findings relating to e‐cigarette posts on social media [53, 54]; however, more research is needed to disentangle how unfavourable attitudes about posting alcohol‐related content online is tied to future drinking behaviour and how that can be leveraged in interventions (e.g., employing influencers for anti‐alcohol campaigns, as has been used with other substances [55]). It is possible that the contrasting positive and negative perceptions of alcohol‐related posts by adolescents in this study highlight the bi‐directional relationship between social media content and adolescent attitudes, such that pre‐existing attitudes about alcohol use influence adolescent reactions to alcohol‐related posts and exposure to alcohol‐related posts influences adolescents' future attitudes about alcohol.…”
Section: Discussionsupporting
confidence: 79%
“…Extending prior research, some participants described negative perceptions of peer‐ and influencer‐generated alcohol content, including that peers may be exhibiting poor judgement and that influencers may be ‘selling out’ or mis‐using their platform. This is consistent with findings relating to e‐cigarette posts on social media [53, 54]; however, more research is needed to disentangle how unfavourable attitudes about posting alcohol‐related content online is tied to future drinking behaviour and how that can be leveraged in interventions (e.g., employing influencers for anti‐alcohol campaigns, as has been used with other substances [55]). It is possible that the contrasting positive and negative perceptions of alcohol‐related posts by adolescents in this study highlight the bi‐directional relationship between social media content and adolescent attitudes, such that pre‐existing attitudes about alcohol use influence adolescent reactions to alcohol‐related posts and exposure to alcohol‐related posts influences adolescents' future attitudes about alcohol.…”
Section: Discussionsupporting
confidence: 79%
“…32-35 In addition, these insights are critical for the effective planning and execution of modern digital media campaigns that rely on interest-based targeting to deliver digital advertisements to the intended audience. 36 Past studies describing ever and current vape users have typically focused on vaping attitudes and beliefs, 37-40 or have used psychographics and motivations to segment adult, but not adolescent, vape users into discrete subgroups. 41,42 Only a few studies have examined the psychographics of adolescent or young adult vape users, revealing that novelty-seeking, sensation-seeking, and lower social conservatism are generally associated with ever and current vaping in these populations.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies related to smoking and alcohol use have shown that young individuals with positive prototypes of someone using a substance are more likely to use themselves ( Aloise-Young et al, 1996 , Blanton et al, 1997 ). One study that inspired the current work and used almost identical questions to those in the current study found that youth ages 14–20 who reported higher willingness to try e-cigarettes or had tried them previously were more likely to report positive attributes of e-cigarette users ( McKelvey et al, 2018 ), demonstrating the impact prototypes may hold for e-cigarette users. These attributes have not, to our knowledge, been examined among young adult e-cigarette users (e.g., above age 20), across different sociodemographic groups, or among young adult military populations at higher risk for tobacco use.…”
Section: Introductionmentioning
confidence: 73%
“…Most current research has focused on beliefs related to consequences of using e-cigarettes, but less about characteristics associated with using e-cigarettes, or what people think about the person using the product. These perceptions may be important because it addresses the schema or “prototype” ( McKelvey et al, 2018 ) a person has assigned users of these products. Past studies related to smoking and alcohol use have shown that young individuals with positive prototypes of someone using a substance are more likely to use themselves ( Aloise-Young et al, 1996 , Blanton et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%